Information systems environmental alignment and business performance: A case study - A. K. Garg; R. J.O. Joubert; R. Pellissier (South African Journal of Business Management, 2005)
The studies to establish the relationship between the external environment and business performance have not produced any conclusive results. Moreover, the field combining environmental uncertainty, information systems (IS) strategy and business performance has not been well explored. Considering the gap in current research, this study conceptualises an information systems environmental alignment model. The model analysed the extent of support provided by IS strategy in the assessment of environmental uncertainty and also examined the impact of IS environmental alignment on business performance. Based on empirical data collected by means of a questionnaire from 22 commercial banks in South Africa (covering more than 90% of the commercial banking sector) and using the Partial Least Squares (PLS) technique, the study validated the IS environmental alignment model and found that banks were using IS support to assess the external environment of business. The results suggest that it is not the IS support or investment in information technology (IT) that impacts on business performance, but rather the effective use of IS support in meeting the information needs of the organisation. The study also found that profitability still remains the key measure of business performance in the banking sector in South Africa. These findings have major implications for IT investment by banks, and for the implementation of IS strategy and general investment in the banking sector. IS environmental alignment is becoming extremely important for business because of the substantial investment in IT and the uncertainty of the business environment.
Keywords: 650